2017
DOI: 10.1016/j.ejmp.2017.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a monolithic silicon detector operating in transmission mode on clinical photon beams

Abstract: The study demonstrated that positioning the MP512T in air between the Linac head and the phantom produced negligible perturbation of the surface dose for D >18 cm, and was completely transparent for 6 MV photon beams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Further experiments will be performed on different topologies of the grating structure, including much thinner gratings. It has been shown that the electron contamination reduces with distance from the linac head [25], [26], hence in the future we will include studies at different SSDs. The trench dimensions and overall thickness of the grating will be optimized to minimize the contribution from contamination electrons to the modulation total signal, allowing the photon signal to be extracted.…”
Section: Discussionmentioning
confidence: 99%
“…Further experiments will be performed on different topologies of the grating structure, including much thinner gratings. It has been shown that the electron contamination reduces with distance from the linac head [25], [26], hence in the future we will include studies at different SSDs. The trench dimensions and overall thickness of the grating will be optimized to minimize the contribution from contamination electrons to the modulation total signal, allowing the photon signal to be extracted.…”
Section: Discussionmentioning
confidence: 99%
“…Note that, in the present study, the MP512 was not modeled into the TPS. Its transmission factor was reported to be in the range from 1.020 to 0.997 for SDDs from 0.3 to 24 cm . However, if clinical use will be considered, it is suggested that transmission factor has to be adequately incorporated into a TPS …”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the MP512 has been characterized as a phantom‐based detector for quality assurance in modern radiotherapy; it was demonstrated to be an accurate dosimeter for the measurement of output factors, percentage depth dose distributions, and lateral‐dose profiles; furthermore, its angular dependence was investigated and corrected for, making it a suitable candidate for quality assurance in arc deliveries . The use of the MP512 as a transmission detector was also assessed . In that study, it was reported that the MP512 in TM increases the surface dose by <25% for a SDD in the range from 0.3 to 18 cm, and by <5% for SDD >18 cm .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations